Aphid–willow interactions in a high Arctic ecosystem: responses to raised temperature and goose disturbance - Mark A. K. Gillespie; Ingibjörg S. Jónsdóttir; Ian D. Hodkinson; Elisabeth J. Cooper (Global Change Biology, 2013)
Recently, there have been several studies using open top chambers ( OTC s) or cloches to examine the response of Arctic plant communities to artificially elevated temperatures. Few, however, have investigated multitrophic systems, or the effects of both temperature and vertebrate grazing treatments on invertebrates. This study investigated trophic interactions between an herbivorous insect ( Sitobion calvulum , Aphididae), a woody perennial host plant ( Salix polaris ) and a selective vertebrate grazer (barnacle geese, Branta leucopsis ). In a factorial experiment, the responses of the insect and its host to elevated temperatures using open top chambers ( OTC s) and to three levels of goose grazing pressure were assessed over two summer growing seasons (2004 and 2005). OTC s significantly enhanced the leaf phenology of Salix in both years and there was a significant OTC by goose presence interaction in 2004. Salix leaf number was unaffected by treatments in both years, but OTC s increased leaf size and mass in 2005. Salix reproduction and the phenology of flowers were unaffected by both treatments. Aphid densities were increased by OTC s but unaffected by goose presence in both years. While goose presence had little effect on aphid density or host plant phenology in this system, the OTC effects provide interesting insights into the possibility of phenological synchrony disruption. The advanced phenology of Salix effectively lengthens the growing season for the plant, but despite a close association with leaf maturity, the population dynamics of the aphid appeared to lack a similar phenological response, except for the increased population observed.